Binhi the Calamba Cultural and Trade Center - Lopez, Marie Raphaelle S. (College of Architecture, University of the Philippines Diliman, 2018)
Strategically located across the New Calamba City Hall, in the Plaza Development containing the Calamba Coliseum and the Rizal Monument, the Calamba Cultural and Trade Center is a development aimed to accommodate the community's social, cultural, tourism and trade activities. The project serves as a jump-off point for tourists to experience Calamba's historical sites, tourist destinations and natural resources with galleries and information centers, interconnected with its community spaces such as workshops, an auditorium, and lecture halls to foster interaction as well as cultivate community involvement and development. These spaces are interspersed with convention facilities and open market spaces for trade shows highlighting local products of entrepreneurs and small businesses of Calamba and neighboring towns while promoting awareness to environmental sustainability and concerns by utilizing systems to manage resources and in a fast-growing city.